Practical access to axially chiral sulfonamides and biaryl amino phenols via organocatalytic atroposelective N-alkylation - Shenci Lu (Nature Portfolio, 2019)
NOBINs and other axially chiral entities have received a great deal of interest in recent years. Here, the authors report the kinetic resolution of racemic amino phenols and the enantioselective preparation of axially chiral N-aryl sulfonamides with excellent level of enantiopurity and broad substrate scope.